Toll-like receptor-guided therapeutic intervention of human cancers: molecular and immunological perspectives - Mukherjee, Suprabhat; Patra, Ritwik; Behzadi, Payam; Masotti, Andrea; Paolini, Alessandro; Sarshar, Meysam (Frontiers in Immunology, 2023)
Cancer is a multifactorial disease wherein involvement of Toll-like receptors (TLRs) is of major importance especially in the context of tumorigenesis and metastasis. In this article, significant findings on the molecular influence of different TLRs in the etiology of human cancers, conception of TLR-targeted therapies, development of TLR-targeting chemo-and immunetherapeutics, their molecular mode of actions as well as clinical trials of these therapeutics across the globe have been reviewed and discussed.